2020
DOI: 10.1080/22221751.2020.1787107
|View full text |Cite
|
Sign up to set email alerts
|

Organizing a COVID-19 triage unit: a Swiss perspective

Abstract: Background: With the rapid global spread of the acute respiratory syndrome coronavirus 2, urgent health-care measures have been implemented. We describe the organizational process in setting up a coronavirus disease 2019 triage unit in a Swiss tertiary care hospital. Methods: Our triage unit was setup outside of the main hospital building and consists of three areas: 1. Pre-triage, 2. Triage, and 3. Triage plus. The Pre-triage checkpoints identify any potential COVID-19infected patients and redirect them to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…In Sichuan, China, a three-level triage was introduced to categorize patients according to the different risk levels[ 116 ]. Other triaging approaches were also reported such as an external triage unit in Switzerland[ 117 ] and a pre-access telephone triage in Italy[ 118 ]. These were supported by evidence from China[ 119 , 120 ] which suggested that the procedure of triaging patients effectively screened patients and identified any high-risk populations.…”
Section: Strategies To Optimize Medical Imaging Service Delivery During Covid-19mentioning
confidence: 99%
“…In Sichuan, China, a three-level triage was introduced to categorize patients according to the different risk levels[ 116 ]. Other triaging approaches were also reported such as an external triage unit in Switzerland[ 117 ] and a pre-access telephone triage in Italy[ 118 ]. These were supported by evidence from China[ 119 , 120 ] which suggested that the procedure of triaging patients effectively screened patients and identified any high-risk populations.…”
Section: Strategies To Optimize Medical Imaging Service Delivery During Covid-19mentioning
confidence: 99%
“…A second positive example is the organization of the triage process outside the main buildings of big hospitals. A Swiss case ( Peros et al, 2020 ) presents a system consisting of three areas, i.e. pre-triage, triage, and triage plus.…”
Section: Applying the Coordination Frameworkmentioning
confidence: 99%
“…The outbreak of the novel coronavirus disease (COVID-19) in December 2019 that later turned into a pandemic has posed a tremendous challenge to different healthcare branches [ [1] , [2] , [3] ], and the immediate need to implement a sanitary regime and impose nationwide quarantines in a number of countries. This has led to a significant economic loss and a reorganized life for approximately 4 billion people under lockdown [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%